Social Psychology in the Philippine Context - Montiel, Cristina Jayme (Archīum Ateneo, 2013)
Students deserve far better than to be only taught traditional social psychology. Those living in non-Western societies have rich histories and distinct normative systems, with their own indigenous social issues and patterns of social life. They have their own distinct needs from social psychology. This volume presents a serious effort to develop social psychology that is “appropriate” for Philippine society, something called for but neglected over many decades.